Effects of Heat Addition on Wave Drag Reduction of a Spiked Blunt Body - Hongyu Wang; Yanguang Yang; Langquan Li; Gang Wang; Qinghu Zhang (International Journal of Aerospace Engineering)
Drag reduction technology plays a significant role in extending the flight range for a high-speed vehicle. A wave drag reduction strategy via heat addition to a blunt body with a spike was proposed and numerically validated. The heat addition is simulated with continuous heating in a confined area upstream of the blunt body. The effects of heat addition on drag reduction in three flow conditions (M=3.98,5,6) were compared, and the influence of power density qh (q1=2.0×108 W/m3, q2=5.0×108 W/m3, and q3=1.0×109 W/m3) of heating was evaluated. Results show that the heat addition has a positive way to reduce the drag of the body with a spike alone, and more satisfactory drag reduction effectiveness can be achieved at a higher Mach number. The drag reduction coefficient increases with qh in the same flow condition, with a maximum of 38.9% (M=6) as q3=1.0×109 W/m3. The wave drag reduction principle was discussed by a transient calculation, which indicates that the separation region has entrainment of the heated air and expanded with its sonic line away from the blunt cone, which results in an alleviation of the pressure load caused by shock/shock interaction.